Multiplex profiling identifies clinically relevant signalling proteins in an isogenic prostate cancer model of radioresistance - Bates, Mark; Manecksha, Rustom; Marignol, Laure; Prina Mello, Adriele (My University, 2019)
The exact biological mechanism governing the radioresistant phenotype of prostate tumours at a high risk of recurrence despite the delivery of advanced radiotherapy protocols remains unclear. This study analysed the protein expression profiles of a previously generated isogenic 22Rv1 prostate cancer model of radioresistance using DigiWest multiplex protein profiling for a selection of 90 signalling proteins. Comparative analysis of the profiles identified a substantial change in the expression of 43 proteins. Differential PARP-1, AR, p53, Notch-3 and YB-1 protein levels were independently validated using Western Blotting. Pharmacological targeting of these proteins was associated with a mild but significant radiosensitisation effect at 4Gy. This study supports the clinical relevance of isogenic in vitro models of radioresistance and clarifies the molecular radiation response of prostate cancer cells.
PUBLISHED
Keywords: Prostate cancer; Prostate tumours; Radioresistance